Systematic review of the effectiveness and cultural adaptation of social skills interventions for adolescents with autism spectrum disorders in Asia - Tawankanjanachot, Nadlada; Melville, Craig; Habib, Abdullah; Truesdale, Maria; Kidd, Lisa (Research in autism spectrum disorders, 2023)
Social skills interventions have been shown to improve social skills in adolescents with autism spectrum disorders (ASD). Because the majority of social skills interventions have been trialled in Western countries, they may not be generalisable to Asian countries with a different cultural background. The purpose of this review was to determine the efficacy and cultural adaptability of social skills interventions for adolescents with ASD (aged 10–19 years) in Asian countries. This review incorporated quantitative and mixed methods published, peer-reviewed research. Five electronic databases were searched. This review followed the PRISMA guidelines. A meta-analysis was conducted by using Revman 5.4 for 3 studies. In total, 15 studies were included in the review (n = 332), conducted across 7 Asian countries. Seven studies had undergone cultural adaptation in 3 countries (e.g., Hong Kong, South Korea, and Israel). Meta-analysis results for three comparable studies showed that the cultural adaptation of social skills interventions improved social skills knowledge of adolescents with ASD. The review identified that social skills interventions for adolescents with ASD in Asian countries, particularly those which have been adapted to adolescents’ cultural needs and preferences, are potentially effective for improving social skills. However, due to the study's limitations and the heterogeneity of included studies, further research is needed to provide strong evidence. •This systematic review aimed to look at existing research on social skills interventions in Eastern countries to see if they were effective and suitable for adolescents from different cultural backgrounds.•Cultural adaptation is important when researchers adapt social skills interventions from Western countries to Asian countries.•Three studies of cultural adaptation of social skills interventions improved the social skills knowledge of adolescents with ASD.•A standardised study and a large sample size are needed in future studies.